Molecular detection of Salmonella enterica serovar Typhi by Vi-qPCR - Shakrin, NNSM; Wahab, AHA; Ramasamy, RP; Yussof, WNW; Noordin, N; Verashahib, K; Jahis, R; Siti Noor Adnalizawati Adnan (Malaysian Soc Microbiology, 2024)
Indexed by WOS/SCOPUS